2018
DOI: 10.1152/ajpregu.00283.2017
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the presence in rainbow trout brain of amino acid-sensing systems involved in the control of food intake

Abstract: To assess the hypothesis of central amino acid-sensing systems involved in the control of food intake in fish, we carried out two experiments in rainbow trout. In the first one, we injected intracerebroventricularly two different branched-chain amino acids (BCAAs), leucine and valine, and assessed food intake up to 48 h later. Leucine decreased and valine increased food intake. In a second experiment, 6 h after similar intracerebroventricular treatment we determined changes in parameters related to putative am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
66
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 39 publications
(78 citation statements)
references
References 70 publications
(103 reference statements)
11
66
1
Order By: Relevance
“…In a previous study (Comesaña et al, 2018) on rainbow trout ( Oncorhynchus mykiss ) as a model teleost fish, we demonstrated that intracerebroventricular (ICV) treatment with leucine decreased food intake as expected whereas valine, contrary to mammals, had a clear orexigenic effect. We related the effects on food intake to the presence of amino acid sensing systems (dependent on metabolism of BCAA, metabolism of glutamine, mTOR, T1R receptors, and GCN2) sensitive to leucine in hypothalamus and telencephalon.…”
Section: Introductionmentioning
confidence: 51%
See 4 more Smart Citations
“…In a previous study (Comesaña et al, 2018) on rainbow trout ( Oncorhynchus mykiss ) as a model teleost fish, we demonstrated that intracerebroventricular (ICV) treatment with leucine decreased food intake as expected whereas valine, contrary to mammals, had a clear orexigenic effect. We related the effects on food intake to the presence of amino acid sensing systems (dependent on metabolism of BCAA, metabolism of glutamine, mTOR, T1R receptors, and GCN2) sensitive to leucine in hypothalamus and telencephalon.…”
Section: Introductionmentioning
confidence: 51%
“…Enzyme activities were assessed at maximum rates after preliminary tests to determine optimal substrate concentrations. BCAT ( EC 2.6.1.42), glutamine synthetase (GLS, EC 6.3.1.2), and GDH ( EC 1.4.1.4) activities were determined as previously described (Comesaña et al, 2018). …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations